POST-DEMOCRACY: DEMOCRATIC MINORITY VERSUS ABSENTEEISM OR THE IMPERATIVE OF DEMOCRATIC MAJORITY? - Laurėnas, Vaidutis (Sociologija. Mintis ir veiksmas, 2015)
The growth of the scale of absenteeism leads to the fact that part of the democracies are ruled, and an even larger number of democracies are approaching the form of rule, when the ruling minority – the representatives – are democratically (?) elected by the minority of the society. In the transformation of the contemporary democracy, the principal issue is not the return of informed and knowledgeable voters, susceptible to inevitable absenteeism, to the political elections, controlled by the “big consensus” of the political parties, business and media, but rather the diversification of the delegation of powers to deal with public problems which would allow the democratic majority to form and become recognized not merely by way of political elections. That can be called post-democracy, and still better, a bifurcation point when one never knows which direction the process may turn. With the growing scale of absenteeism, the political science models the transfer of the accents of political participation and the majority of the society, necessary for democracy, from the stage of politics to the stage of policy. That is the case of the permanent quest for the harmony of the representative and direct democracies. By means of contemporary information and communication technologies, it is necessary to learn to qualitatively establish the preferences of solution of specific public problems of those citizens who participate in public life in other ways and more independently than in political elections, i.e., of the neo-majority. As much as we are unable to cope with the issue, as much de-democratisation is possible. Democratic minority tends to degenerate sooner or later.